2008
DOI: 10.1161/strokeaha.107.491241
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Clinical Impact of Microembolic Signals During or After Cardiosurgical Procedures

Abstract: Background and Purpose-Microembolic signals (MESs) are detectable within the transcranial Doppler frequency spectrum downstream from vascular atherothrombotic or cardiothrombotic lesions. A frequent occurrence of MESs has also been shown during bypass surgery or after mechanical valve implantation. We sought to compile the knowledge on MES prevalence, the clinical impact of these cardiogenic MESs, and microemboli composition. Summary of Review-We performed a systematic MEDLINE search and summarized the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
3

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 113 publications
0
26
0
3
Order By: Relevance
“…These results provide important novel insight into the mechanisms of CE associated with TAVI and support the need for further research to both reduce the incidence of CE during these procedures and better determine their clinical relevance. (J Am Coll Cardiol 2011;57: [18][19][20][21][22][23][24][25][26][27][28] …”
Section: Discussionmentioning
confidence: 99%
“…These results provide important novel insight into the mechanisms of CE associated with TAVI and support the need for further research to both reduce the incidence of CE during these procedures and better determine their clinical relevance. (J Am Coll Cardiol 2011;57: [18][19][20][21][22][23][24][25][26][27][28] …”
Section: Discussionmentioning
confidence: 99%
“…We used the terms, ''microemboli'', ''microembolic signals'', ''cerebral microemboli'', ''High Intensity Transient Signals''; those manuscripts with extensive bibliographic information were selected to look for further papers related to the topic. We focused on papers reporting MES in non-cardiovascular diseases after exclusion of aortic, carotid, and cerebral atheromatous disease, dissection and endarterectomy; cardiac diseases and procedures, including patent foramen ovale, prosthetic heart valves, ventricular assist devices, cardiopulmonary bypass, coronary angiography or stent placement, for which comprehensive reviews have been published recently [14,36]. In this review, for each pathological condition, we give a brief introduction supporting the argument to look for MES, we state the postulated role of MES in the pathogenesis of each disorder and possible developments in the research field.…”
Section: Methodsmentioning
confidence: 99%
“…5,8,9,13 Some studies have found that patients undergoing CABG with higher HITS counts were more likely to experience cognitive deficits 1,2,5,6 or higher rates of frontal lobe dysfunction, 16 but others have found that there is no correlation between HITS counts and neurological symptoms or cognitive deficits. 6,8,17 Several methodological issues may account for the variability among these studies, including small sample sizes, 1,6 differences in intensity thresholds used to detect HITS, 13 artery location (carotid versus middle cerebral artery), 1,8,12 unilateral or bilateral recordings, 2,8,12 type of ultrasound device, 13,18 quality of TCD recordings, 18 inconsistency of signal reviewing techniques (automatic versus manual), 13,18 and the effects of several confounding variables such as the duration of CPB and core body temperature. 2 We sought to overcome these limitations by studying a large number of low-risk patients undergoing †HITS were recorded unilaterally in the left common carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…5 This technology detects cerebral emboli by the ultrasonic characteristics of the embolus-blood interface in the form of high-intensity transient signals (HITS). 5,6 Although a large number of HITS occur during CPB, there are no large studies confirming that these embolic signals are correlated with POCD.…”
mentioning
confidence: 99%
See 1 more Smart Citation